2013
DOI: 10.1097/hcr.0b013e31828254fc
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Discrepancies Between Obesity by Body Mass Index and Body Fat in Patients With Coronary Heart Disease

Abstract: Even though a correlation exists between BMI and BF, they frequently classify individuals differently in a population of CHD patients. When defining overweight/obesity, care must be taken when using a crude screening tool such as BMI. While it is not expected for all clinicians to add BF assessments within routine patient assessments, the results of this study may be helpful to guide clinicians and researchers who are considering different aspects of body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 38 publications
0
23
1
3
Order By: Relevance
“…Overall, the inability of BMI to discriminate between fat‐free mass, a protective factor, and fat mass, a factor associated with adverse outcomes, may lead to erroneous assumptions about risk of MACEs in patients with CAD and may explain why, in our cohort, BMI was not associated with MACEs 5, 6, 26, 27. Thus, the results of our study could not confirm the obesity paradox that has been reported in several other studies in those with CAD,28, 29, 30, 31, 32 heart failure,33, 34, 35, 36 and atrial fibrillation 37.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Overall, the inability of BMI to discriminate between fat‐free mass, a protective factor, and fat mass, a factor associated with adverse outcomes, may lead to erroneous assumptions about risk of MACEs in patients with CAD and may explain why, in our cohort, BMI was not associated with MACEs 5, 6, 26, 27. Thus, the results of our study could not confirm the obesity paradox that has been reported in several other studies in those with CAD,28, 29, 30, 31, 32 heart failure,33, 34, 35, 36 and atrial fibrillation 37.…”
Section: Discussionmentioning
confidence: 94%
“…The obesity paradox was addressed in a large meta‐analysis of patients with CAD, where it was observed that subjects with a low BMI had an increased relative risk for total mortality and cardiovascular mortality, whereas obese patients had no increased risk or even a lower risk for total mortality or cardiovascular mortality 3. Results showing the obesity paradox could be partially explained by the poor diagnostic accuracy of BMI to detect adiposity and its inability to differentiate between fat‐free and fat mass, particularly among patients with CAD 5, 6, 20. For example, a lower BMI could be related to sarcopenia rather than low fat mass, while being overweight may reflect increased muscle mass, rather than excessive adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports documented the efficacy of BMI on reflecting body fat and concluded that BMI correlates with the body fat amount and is still the most practical and commonly used test for defining obesity (4).…”
Section: Discussionmentioning
confidence: 99%
“…Even though BMI and waist circumference are the most frequently used obesity indices, they can poorly differentiate regional fat distribution and therefore, are critiqued for their accuracy in defining obesity [13] . Visceral adiposity has been demonstrated to be associated with increased risk of atherosclerotic cardiovascular diseases even after adjustment for BMI and other clinical risk factors [14,15] .…”
Section: Baseline Data Collectionmentioning
confidence: 99%